2009
DOI: 10.1037/a0015085
|View full text |Cite
|
Sign up to set email alerts
|

A perceptual process approach to selecting color scales for complex visualizations.

Abstract: Previous research has shown that multicolored scales are superior to ordered brightness scales for supporting identification tasks on complex visualizations (categorization, absolute numeric value judgments, etc.), whereas ordered brightness scales are superior for relative comparison tasks (greater/less). We examined the processes by which such tasks are performed. By studying eye movements and by comparing performance on scales of different sizes, we argued that (a) people perform identification tasks by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…The model accounted for 87% and 66% of the variance in reaction times for two different graph formats and demonstrated that a less familiar graph (parametric graph) that is better tuned to the task requirements can be more effective than a more familiar type (function graph). Similarly, Trafton and colleagues (Breslow et al, 2009;Trafton et al, 2000) have used a combination of task analysis, cognitive modeling, eye-tracking, and verbal protocols to study how people extract information from geospatial displays, integrate information across different displays and variables, and to explain interactions between tasks and display format.…”
Section: How Cognitive Models Inform Display Designmentioning
confidence: 99%
“…The model accounted for 87% and 66% of the variance in reaction times for two different graph formats and demonstrated that a less familiar graph (parametric graph) that is better tuned to the task requirements can be more effective than a more familiar type (function graph). Similarly, Trafton and colleagues (Breslow et al, 2009;Trafton et al, 2000) have used a combination of task analysis, cognitive modeling, eye-tracking, and verbal protocols to study how people extract information from geospatial displays, integrate information across different displays and variables, and to explain interactions between tasks and display format.…”
Section: How Cognitive Models Inform Display Designmentioning
confidence: 99%
“…First, it explicitly differentiates between two aspects of color vision: the activity in the yellow-blue mechanism (a qualitative aspect, measured through h uv ) and the activity in the achromatic mechanism (a quantitative aspect, measured through L R ). It must be remembered that each of these aspects is usually associated with a different color use (Breslow et al, 2009). Second, this makes it easier to understand the consequences of a simulation error.…”
Section: Discussionmentioning
confidence: 99%
“…Color variations are frequently used to facilitate some visual tasks (Breslow, Trafton, & Ratwani, 2009;Yamani & McCarley, 2010). They include the localization (Remington, Johnston, Ruthruff, Gold, & Romera, 2000) and identification (Spence, Kutlesa, & Rose, 1999) of some kind of information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicolored scale with a distinct color at each pressure level was chosen, as multicolored scales are preferred for identification tasks (i.e. identifying areas of the breast which have not been palpated with low, medium and high pressure) [7]. The colors chosen for each pressure level are influenced by prior information visualization literature and discussion with medical educators.…”
Section: Touch Mapmentioning
confidence: 99%